New graduate registered nurses' professional competence and the impact of preceptors' education intervention: a quasi-experimental longitudinal intervention study - Lindfors Kirsi; Flinkman Mervi; Kaunonen Marja; Huhtala Heidi; Paavilainen Eija (BMC, 2025)
Aims and objectives: The aim of this quasi-experimental longitudinal intervention study was to investigate new graduate nurses' professional competence development after preceptors' participation in an education intervention.
Background: New graduate registered nurses are expected to be competent in many areas of nursing. Expectations that are sometimes unrealistic may cause a sense of inadequacy and stress, and this may in turn prevent them from fully deploying their competencies. Competence development is related to practice environment, occupational commitment, empowerment, and work experience. Orientation or transition programs have been designed to ensure new graduate nurses' competence, and preceptors and preceptorship could also have significant influence on their competence development.
Design: A quasi-experimental longitudinal intervention study.
Methods: The data was collected from October 2015 to November 2017. Participating wards were randomized into intervention and control groups. The intervention group preceptors had an eight-hour education intervention that focused on new employees' orientation, particularly from new graduates' point of view. Wards in the control group continued to precept as before. The Nurse Competence Scale was used for new graduates' self-assessment at baseline and at three-month and nine-month follow-up. This study is reported in accordance with the TREND Statement Checklist.
Results: The education intervention aimed at preceptors did not have impact on the intervention group NGRNs' competence development. There were no statistically significant differences between the groups and effect size remained small.
Conclusions: The preceptors' education intervention was not effective enough to develop new graduates' professional competence so that it would have differed from that of the graduates receiving conventional orientation at the university hospital. This study confirmed that competence development is a complex and multidimensional phenomenon and organizations should invest in new graduate registered nurses' competence development during their early career. Preceptors' education and development of preceptorship and transition programs are an important part of overall competence development in complex health care environments.